Effect of attachment types and number of implants supporting mandibular overdentures on stress distribution: A computed tomography-based 3D finite element analysis - Bilhan Arat, Selda; Baykasoğlu, Cengiz; Bilhan, Hakan; Kutay, Ömer; Muğan, Ata (Elsevier, 2015)
The objective of this study was to calculate stresses in bone tissue surrounding uncoupled and splinted implants that are induced by a bite force applied to the mandible and to determine whether the number of mandibular overdenture supporting implants in mandibular bone influence the stress distribution. A human adult edentulous mandible retrieved from a formalin fixed cadaver was used to define the geometry of finite element (FE) model and the FE model was verified with experimental measurements. Following the FE model validation, three different biting situations were simulated for the 2-, 3- and 4-implant retentive anchor as well as bar attachment overdentures under vertical loading of 100 N. As a result of the analyses, it was concluded that an increment in implant number and the splinted attachment type tended to cause lower stresses and the use of two single attachments seems to be a safe and sufficient solution for the treatment of mandibular edentulism with overdentures.
Keywords: Mandibular Overdenture; Finite Element Analysis; Attachment Type; Number of Implants; Stress Distribution; Biomechanics